Utilization of work place based assessment tools in medical education: Potential challenges and solutions - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Tabriz University of Medical Sciences, 2020)
From a medical graduate perspective, the field of medicine is quite complex: graduates will encounter a wide range of healthcare scenarios to which they must respond using a professional,competent and skillful approach. Workplace-based assessment (WPBA) tools are a unique form of assessment to evaluate the performance of the medical student in the workplace in real time and has been linked with multiple benefits. However, adoption of WPBA by medical colleges has not been uniform owing to multiple challenges related to feasibility, students and faculty members. In order to facilitate the successful implementation of WPBA tools, medical educators must work as a team in a coordinated manner and ensure that all the stakeholders are part of the process. In conclusion, WPBA have a special role in the making of a competent and professional health care professional. However, the process of employing WPBA tools is a challenging task and its use requires us to be thoughtful and planned in our approach to accomplish the intended learning outcomes.